2016
DOI: 10.1074/jbc.m116.746420
|View full text |Cite
|
Sign up to set email alerts
|

Bipartite Role of Heat Shock Protein 90 (Hsp90) Keeps CRAF Kinase Poised for Activation

Abstract: Edited by Velia FowlerCRAF kinase maintains cell viability, growth, and proliferation by participating in the MAPK pathway. Unlike BRAF, CRAF requires continuous chaperoning by Hsp90 to retain MAPK signaling. However, the reason behind the continuous association of Hsp90 with CRAF is still elusive. In this study, we have identified the bipartite role of Hsp90 in chaperoning CRAF kinase. Hsp90 facilitates Ser-621 phosphorylation of CRAF and prevents the kinase from degradation. Co-chaperone Cdc37 assists in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 112 publications
2
28
0
Order By: Relevance
“…The largest increase in median lifespan was observed for daf-21, the C. elegans ortholog of human HSP90. Although it has been previously reported to increase lifespan (Sutphin et al, 2017;Horikawa et al, 2015), this is the first study to demonstrate its translational regulation in the context of DR. DAF-21/HSP90 serves to promote growth and reproduction by keeping growth-related kinases and transcription factors in a near-native conformation that facilitates their activation (Mitra et al, 2016). HSP90 also sequesters the HSF-1 heat shock transcription factor, inhibiting its ability to trimerize and upregulate expression of heat shock protein genes (Zou et al, 1998) .…”
Section: Discussionmentioning
confidence: 99%
“…The largest increase in median lifespan was observed for daf-21, the C. elegans ortholog of human HSP90. Although it has been previously reported to increase lifespan (Sutphin et al, 2017;Horikawa et al, 2015), this is the first study to demonstrate its translational regulation in the context of DR. DAF-21/HSP90 serves to promote growth and reproduction by keeping growth-related kinases and transcription factors in a near-native conformation that facilitates their activation (Mitra et al, 2016). HSP90 also sequesters the HSF-1 heat shock transcription factor, inhibiting its ability to trimerize and upregulate expression of heat shock protein genes (Zou et al, 1998) .…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that C-RAF autophosphorylation at Serine 621 stabilizes C-RAF,inhibiting its degradation by the proteasome [ 40 ]. Interestingly, in the absence of Serine 621 phosphorylation, C-RAF is degraded by the proteasome by mechanisms that involves an unknown E3 ubiquitin ligase [ 40 41 ]. Our results are compatible with the participation of HERC1 in this model, where C-RAF is marked with a polyubiquitylation signal for degradation by the proteasome.…”
Section: Discussionmentioning
confidence: 99%
“…Most identified HSP90 clients are proteins related to biological processes dysregulated in cancer, such as signal transduction, survival, growth and invasiveness of cells and include steroid hormone receptors, both wild-type and mutant forms of the tumor suppressor p53, telomerase, hypoxia-inducible factor 1α (HIF1α) (12) and kinases, which display a continuous range of binding affinities for HSP90 (83). Some kinases would require HSP90 to stabilize their open conformation in order to efficiently bind ATP, whilst others seem to only need HSP90 for initial folding (27,84) and would perform their enzymatic activity without HSP90 assistance. Studies with closely related pairs of client/non-client kinases, like the client v-Src and the non-client c-Src, which share 98% sequence identity, suggest that HSP90 dependence requires a combination of factors, including folding cooperativity and subtle changes in the overall stability and compactness of clients (85).…”
Section: Hsp90 Chaperones In Cancermentioning
confidence: 99%